The Role of Job Characteristics in Nurses' Willingness to Customer Oriented Behaviors - SM Dibaji; S Shahpoori; A Nouri (Iran University of Medical Sciences, 2013)
Abstract   Background & Aim: Client centered behaviors and customer orientation are new issues in nursing and hospital literature. The aim of current study was to investigate the role of job characteristics in customer oriented behaviors among nurses.   Material and Methods: It was across-sectional, correlational study. A total of 150 nurses of Alzahra hospital of Isfahan were recruited by stratified random sampling and completed Sims et al., job characteristics Inventory (1976) and Kim et al., Willingness to Customer Oriented Measure (2004). Data was analyzed by descriptive statistics, Pearson's correlation and stepwise multiple regression using SPSS-PC (v.16).   Results: The findings revealed that except autonomy and friendship, all of job characteristics are associated with willingness to customer oriented behaviors (P<0.05). However, using stepwise regression analysis, just job feedback in first step (F= 18.473, P<0.05) and job variety in second step (F=13.507, P<0.05) could predict customer oriented behaviors.   Conclusion: According to the findings, it seems necessary to design the nurse's task so that nurses can be aware of the outcome of their performance. Also, making variation in the tasks assigned to nurses by methods like job enlargement, job enrichment and job rotation can lead to willingness to behaviors that satisfy patient and their guardians.   Received: 26 May 2013   Accepted: 28 Aug 2013 .